2016
DOI: 10.1186/s13256-016-0928-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute neck pain caused by pseudogout attack of calcified cervical yellow ligament: a case report

Abstract: BackgroundCalcification of the yellow ligament sometimes compresses the spinal cord and can induce myelopathy. Usually, the calcification does not induce acute neck pain. We report a case of a patient with acute neck pain caused by calcium pyrophosphate dihydrate in a calcified cervical yellow ligament.Case presentationA 70-year-old Japanese woman presented with acute neck pain. She had a moderately high fever (37.5 °C), and her neck pain was so severe that she could not move her neck in any direction. Compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 6 publications
3
18
0
Order By: Relevance
“…Literature has shown that acute neck pain could be caused by CPPD crystal-induced arthritis of the lateral atlantoaxial joint [ 17 ]. In addition, Kobayashi et al [ 18 ] reported a case with acute neck pain that resulted from CPPD attack of the cervical ligamentum flavum without facet arthritis. Although we can not conclude that neck pain in our case series is due to CPPD deposition in ligamentum flavum, acute neck pain should be considered a symptom for the diagnosis of CPPD deposition disease.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that acute neck pain could be caused by CPPD crystal-induced arthritis of the lateral atlantoaxial joint [ 17 ]. In addition, Kobayashi et al [ 18 ] reported a case with acute neck pain that resulted from CPPD attack of the cervical ligamentum flavum without facet arthritis. Although we can not conclude that neck pain in our case series is due to CPPD deposition in ligamentum flavum, acute neck pain should be considered a symptom for the diagnosis of CPPD deposition disease.…”
Section: Discussionmentioning
confidence: 99%
“…Acute neck pain and fever are often caused by crowned dens syndrome or by crystal-induced arthritis of the lateral atlantoaxial joint in the elderly [3]. We previously reported a case of acute neck pain caused by pseudogout attack of calcified cervical ligamentum flavum [3]. There have been some reports of spinal canal stenosis due to CPPD crystal deposition [4].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is one of the risk factors for pseudogout, and the elderly population is rapidly increasing in Japan [2]. Calcification of the ligamentum flavum sometimes causes acute neck pain and compression of the spinal cord [3], which can induce myelopathy [4]. However, there are few reports of acute exacerbation of myelopathy due to a pseudogout attack of the cervical ligamentum flavum, and there are no reports of that after a cervical spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal involvement of calcium pyrophosphate arthritis is uncommon but has been reported 4 5. CPP crystals have been found in many spinal structures, including the intervertebral discs, synovium, articular cartilage, bursae and ligaments.…”
Section: Introductionmentioning
confidence: 99%